Effects of maturity status on anthropometric measures, physical fitness, and training load in young Brazilian soccer players - Alves Ferreira Da Silva, Marcelo Henrique (2021)
Purpose. The study aimed to (1) verify maturity status effects on training performance indicators in young soccer players; (2) compare the anthropometric, physical fitness, and training performance indicators before and after 10-week training; (3) investigate relationships between anthropometric measures, maturity status, and performance indicators. Methods. The study involved 34 male soccer players (aged 17 ± 2 years). Biological maturation was determined by skeletal age, with left hand radiology. Body height, mass, and adiposity were determined. Physical fitness was measured with field tests, including intermittent aerobic fitness, repeated sprint ability, and lower limb power. The participants were monitored daily over 10 weeks (preseason) through rating of perceived exertion. Results. Average maturity players showed greater training load (p = 0.04) and physical training volume (p = 0.04) than early maturity players. Mature players presented higher physical training volume than early maturity players (p = 0.04). We verified better performances in intermittent aerobic fitness (p < 0.001, d = 1.086), vertical jump (p = 0.007, d = 0.584), best sprint time (p = 0.003, d = 0.661), average sprint time (p = 0.002, d = 0.676), and sum of the sprint times (p = 0.002, d = 0.675) after the 10-week preseason. Physical and technical-tactical training volumes were moderately-largely related to best sprint time (r = –0.48, r = –0.55, respectively). Technical-tactical training volume was largely related to intermittent aerobic fitness (r = 0.54). Conclusions. Advanced maturity and mature players presented greater training load and physical training volume than early maturity subjects. Players exhibited improved physical fitness after the 10-week preseason. Technical-tactical training volume showed a large association with the intermittent aerobic fitness test.